Kajian Kearifan Lokal Masyarakat Desa Ngadas Terhadap Pengembangan Ekowisata di Taman Nasional Bromo Tengger Semeru Jawa Timur - fahrizal gifari; Tatag Muttaqin; Ramli Ramadhan (Journal of Forest Science Avicennia, 2019)
ABSTRACT  Bromo Tengger Semeru National Park (TNBTS) is a complex area of approximately 50,276 Ha in the mountainous region, covering three famous landscapes namely Mount Bromo, Tengger Caldera and Mount Semeru. Based on the Decree of the Director General of PHKA No. 68 / Kpts / Dj-VI / 1998, TNBTS zoning consists of: Core Zone 22,006 Ha; Jungle Zone 23.485,20 Ha; Intensive Use Zone 425 Ha; Traditional Use Zone 2,360 Ha; and the 2,000 Ha Rehabilitation Zone.This study aims to examine the local wisdom adopted by the community in Ngadas Village. When the research began in June-July 2019 and the research method used was a qualitative method, using the Phenomenology approach. An interesting phenomenon of research is the existence of Bromo Tengger Semeru National Park, Poncokusumo District, Malang Regency. Data collection techniques using in-depth interviews and closed questionnaires, observation and study of documents or literatureThe majority of Ngadas people belong to the Tengger tribe, a tribe that is also scattered in villages near Mount Bromo in Pasuruan and Probolinggo districts where the majority of Tengger are Hindu. The Ngadas community has several traditional events such as Karo, Kasada, and Unan-unan.